Multiscale 2D/3D microshaping and property tuning of polymer-derived SiCN ceramics. Issue 5 (May 2022) - Hagelüken, Lorenz; Sasikumar, Pradeep Vallachira Warriam; Lee, Ho-Yun; Di Stadio, David; Chandorkar, Yashoda; Rottmar, Markus; Maniura-Weber, Katharina; Blugan, Gurdial; Brugger, Juergen
Abstract: Polymer-derived ceramics exhibit excellent properties and are compatible with many shaping techniques due to their liquid precursors. We present a fast and pressureless process for the fabrication of SiCN. Using varied amounts of the filler divinyl benzene, defect-free monolithic disc samples are obtained at high yields. Their electrical conductivity is adjustable across 10 orders of magnitude, flexural strength is improved up to 1.7 GPa, and cytocompatibility is demonstrated. This processing route is applied to a new multiscale microshaping method combining the advantages of two-photon polymerization and casting. The parts' general shape is defined by KOH-etched silicon molds whereas individual freeform microfeatures like a 3D QR code are implemented through sacrificial 2PP photoresin microstructures added to the mold. The green body is pyrolyzed directly in the mold, whereby the photoresin decomposes and the ceramic part with the submicrometer resolution features imprinted releases itself from the mold undamaged due to ∼30% shrinkage.